Effect of Slab Existence on Settlement-Time Curve of Soft Clayey Deposit Improved by Floating Soil-Cement Column - พงศ์ศิวะสถิตย์ ศุภสิทธิ; มั่นใจ สมพร; ปิยะพิพัฒน์ สุธี (Frontiers in Engineering Innovation Research, 2015)
Large scale laboratory model tests (diameter of 0.45 m and height of 1.0 m) were conducted to investigate the consolidation behavior of floating soil-cement column improved soft clayey model grounds with or without a cement stabilized slab on the ground surface. The aim of study is to investigate the influence of slab existence on the settlement-time curve. Two cases of testing were conducted as without slab and with slab of 25 cm in thickness. Bangkok clay was used as soft clayey deposit for investigation. There are 3 steps of testing as 1) Making ground 2) Soil-cement column installation 3) Consolidation test. The consolidation pressure applied 120 kPa for 2 cases. The other parameters as the area improvement ratio and the depth improvement ratio were fixed. Test results show that the consolidation settlement of with slab of 25 cm in thickness case is less than that of without slab case significantly. Then the method of calculating the settlement-time curve by Pongsivasathit et al. (2012) was applied to the 2 cases of laboratory model. As results, for with a slab on ground surface, this method overestimated. The method for calculating the settlement-time curve by Pongsivasathit et al.(2012) is essential to be modified which can consider the effect of cement stabilized slab.